Staged approach for upper extremity chronic ischemia in high-performing athlete with arterial thoracic outlet syndrome - Caroline E. Minnick, BS; Lindsay Lynch, MD; Kevin Chang, MD; Ashlee Stutsrim, MD; Julie Freischlag, MD; Matthew Goldman, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Arterial thoracic outlet syndrome is a rare condition characterized by subclavian artery compression, leading to occlusion, poststenotic dilation, aneurysm formation, and distal embolization. We present the case of a 21-year-old collegiate volleyball player with arterial thoracic outlet syndrome and chronic limb-threatening ischemia owing to bilateral cervical ribs. Initially misdiagnosed as Raynaud's phenomenon, she experienced progressive ischemic symptoms. A staged surgical approach included thoracic outlet decompression followed by axillary-to-radial artery bypass without the need for axillosubclavian arterial reconstruction. She returned to collegiate athletics with successful arterial remodeling and graft patency.